Avaliação do Programa de Autonomia Escolar a partir da participação dos conselhos escolares do município de Maracanaú-CE - Jales, Francisca Ticiane Gondim da Costa (2024)
This paper is the result of a proposal to evaluate the School Autonomy Program based on the participation of school councils in the municipality of Maracanaú - CE. The School Autonomy Program is an educational policy that seeks to strengthen the management of schools, granting them greater autonomy in making administrative and pedagogical decisions,with a view to improving the quality of education. The general objective of this qualitativestudy was to evaluate the School Autonomy Program based on the participation of the school councils in the municipality of Maracanaú - CE, with the following specific objectives: I) to analyze the institutional trajectory of the School Autonomy Program in the municipality of Macaranaú; II) to understand the role and function of the School Council within the Executing Units; and III) to investigate the process of financial execution of the School Autonomy Program under the deliberations of the School Council. To this end, we followed the perspective of the In-Depth Evaluation by Rodrigues (2016), with emphasis on three of its axes, namely: trajectory/temporality, content and territorial spectrum/temporality. Bibliographical, documentary and field research were used. The field research was conducted in the municipality of Maracanaú, located in the metropolitan region of Fortaleza/Ceará, through semi-structured interviews, reaching the participation of fifteen subjects linked to the school councils of the six regions of Maracanaú-CE. Data analysis was guided by Bardin's (2016) content analysis technique.The results reveal significant advances in school autonomy and the quality of education in Maracanaú after the implementation of the School Autonomy Program.However, there are still challenges to be faced and areas to be improved, requiring a continuous process of evaluation and improvement of the program.Furthermore, the analysis of the role of the school councils in the Executive Units highlights their fundamental importance in the democratic management of schools, although it also reveals challenges and complexities in their operation.The active and informed participation of council members is crucial to guaranteeing transparent and responsible management of the resources allocated to education, promoting the development and success of the school.